Oil palm smallholders and its sustainability practices in Malaysia - Abazue, C. M; Er, A. C; Ferdous Alam, A. S. A.; Begum, Halima (MCSER Publishing, Rome-Italy, 2015)
The demand for Palm oil has increasing over the several decades and it has led to criticisms and question about sustainability on biodiversity loss, water pollution and deforestation.This study aims to explore the sustainability of oil palm smallholders in Malaysia based on environmental, social and economic perspectives.The aim of the study is to examine the sustainability of smallholding scheme in Malaysia.A questionnaire survey was conducted with 50 smallholders in Terengganu state under the Federal Land Development Authority of Malaysia (FELDA).It’s revealed that most of the smallholders have sufficient knowledge of sustainability consistent with Roundtable on Sustainable Palm Oil (RSPO) and other local agricultural laws practices. The study also indicates that on social aspect, the smallholders have better quality of life through the provision of basic facilities.The study concludes that there is a high degree of sustainability amongst oil palm smallholders under the management of FELDA.